The Role of Community Counselor in Handling Child Clients in Class I Correctional Center of Medan - Penny Naluria Utami (Jurnal Penelitian Hukum De Jure, 2022)
The existence of laws against children must be considered and must be led to be more responsible for themselves, because children are different from adults. Children are teenagers, human resources, and have the potential to continue the life of the nation and state. The child client is then guided to improve himself and his behavior in the existing reality, with the aim of changing his lifestyle, and assisted in behavioral restructuring, especially for clients with severe personality problems that take a long time to resolve. In other words, probation officers can educate a child client about the rejections they will face when receiving changes or feedback from others, while encouraging them to motivate themselves, accept their situation, and change what the child client is going through.  Another important thing that must be done in dealing with child client is to involve the family of the child to participate in the process of handling the child who violates the law.